Cash Waqf Behavior: Explaining Financial Consciousness and The Moderating Role of Religiosity - Lestari, Irna Puji; Pambekti, Galuh Tri; Annisa, Arna Asna (Universitas Islam Internasional Indonesia, 2023)
The role of cash waqf in empowering the economy of Muslims needs to be continuously improved. This study assesses individuals’ behavior towards cash waqf from a behavioral finance perspective by proposing four elements of financial consciousness: financial locus of control, financial capability, financial willingness, and financial sophistication in encouraging cash waqf behavior. This study also investigates the moderating role of religiosity as a Muslim-specific internal factor. Data was collected from a questionnaire of 337 Muslim government employees in the Ministry of Religious Affairs of Indonesia. The Partial Least Square was used to analyze the data. The findings show that financial locus of control, financial capability, financial willingness, financial sophistication, and religiosity have a significant positive influence on individual behavior towards cash waqf. The findings also suggest that religiosity moderates the financial locus of control, as well as financial sophistication, on cash waqf. This implies that initiatives to increase Muslim participation in cash waqf should be embedded in behavioral finance patterns through a combination of financial consciousness and religiosity.